Potential of Anaerobic Bacteria in Bioremediation of Polluted Environments with Organic Waste - Valentina Yasmine; Zitni Irfan Falah; Sheila Meilina Wihandi; Sefia Stefani; Alfi Nur Permatasari; Widya Hamidah; Malwira Raka Zain; Hery Irawan (PT. Gyandharma Global Media, 2025)
Bioremediation is an environmentally friendly approach to addressing pollution, particularly that caused by organic waste. Anaerobic bacteria play an important role in this process, especially in oxygen-depleted environments such as sediments and wastewater. This study aims to identify the role and mechanisms of anaerobic bacteria in the bioremediation process. The results of the study indicate that various types of bacteria, such as methanogens, sulfate reducers, hydrolytic bacteria, acidogenic bacteria, and acetogenic bacteria, are capable of breaking down complex organic compounds into simpler and safer compounds. Additionally, some species also play a role in addressing heavy metal contamination through biosorption and bioprecipitation processes. Metabolic processes such as fermentation, acetogenesis, and methanogenesis are key to the success of anaerobic bioremediation. This indicates that the utilization of anaerobic bacteria can serve as a sustainable, effective solution that aligns with the principles of a circular economy.